Ordered mesoporous Fe-Al2O3 based-catalysts synthesized via a direct "one-pot" method for the dry reforming of a model biogas mixture. (7th June 2019) - Jabbour, Karam; Saad, Ali; Inaty, Lena; Davidson, Anne; Massiani, Pascale; El Hassan, Nissrine
Abstract: Biogas plays a vital role in the emerging renewable energy sector and its efficient utilization is attracting significant attention as an alternative energy carrier to non-renewable fossil fuel resources. Since biogas consists mainly of CH4 and CO2, dry reforming of methane arises as an appropriate process enabling its chemical conversion to high-quality synthesis gas (syngas: H2 and CO mixtures). In this study, we synthesized via a direct "one-pot" method following an evaporation-induced self-assembly approach, ordered mesoporous Fe10%, Ni5% and Fex% Ni(1-x) (x: 2.5, 5 or 7.5%) in Al2 O3 as catalysts for syngas production via dry reforming of a model biogas mixture (CH4 /CO2  = 1.8, at a temperature of 700 °C). Monometallic Fe10% Al2 O3 catalyst presented lower reactivity levels and slightly deactivated during catalysis compared to stable Ni5% Al2 O3 . According to physico-chemical characterization techniques, the incomplete reduction of Fe2 O3 into Fe3 O4 rather than Fe 0 nanoparticles (catalytically active) coupled with the segregation of Fe3 O4 oxides were the main factors leading to the low performance of mesoporous Fe10% Al2 O3 . These drawbacks were overcome upon the partial substitution of Fe by Ni (another transition metal) forming specifically bimetallic Fe5% Ni5% Al2 O3 displaying reactivity levels close to thermodynamic expected ones. The formation of Fe-Ni alloys stabilized iron inside alumina matrix and protected it from segregation. Along with the confinement effect, spent catalyst characterizations showed high resistance towards coke deposition. Graphical abstract: Image 1 Highlights: One-pot synthesis directly yields well-structured mesoporous Fe in Al2 O3 catalysts. Fe10% Al2 O3 are promising, cost-efficient, catalysts for biogas dry reforming. Fe segregation into strips owing to incomplete reduction induces reactivity loss. Partial substitution of Fe by Ni promotes reactivity by reducing Fe segregation.